Scientific substantiation and development of measures of eutrophication control - Авраменко, Н. І. (Scientific Progress & Innovations, 2012)
The main factors that help to reduce the number of bluegreen algae are considered. The intensity of the process of eutrophication of water in the river Vorskla has been established. The optimal conditions for cyanobacteria have been determined. The results of studies on examination of the impact of various chemicals on the reproduction of microorganisms have been presented. Eutrophication processes of the Vorskla River from which agroecological information was collected have been characterised. The number of blue-green algae has been specified. The measures on control of eutrophication process of water in the river Vorskla have been developed.